CARACTERIZAÇÃO GEOFÍSICA DA COBERTURA DETRITO-LATERÍTICA EM SÃO GABRIEL DO OESTE, MS - odirlei neumann (2023)
This present research details detritus-lateritic coverage (TQdl) existing in the area of São Gabriel do Oeste plateau, Mato Grosso do Sul estate in the Chapadão area of São Gabriel do Oeste-MS, of fundamental economic importance for agriculture in the region, highlighting the associated lateritic cangas, widely used in the primary coating of more than 3000 km of municipal highways. In addition, it seeks to evaluate the effectiveness of the GPR geophysical method in lateritic cangas identification in the subsurface and in the detection of the lithological contacts of this formation with the underlying layers, with the generation of an isopach map. Focusing on the continuity of Serra Geral formation in the study area, obtaining the respective isopach map. Complementarily, a preliminary characterization of the aquifer related to the TQdl coverage, not yet individualized, was carried out. To achieve these objectives, the methodology used was to obtain primary data with the GPR, combined with existing geological and geophysical data on the area, which were reprocessed and reinterpreted, mainly from a report by the National Water and Sanitation Agency (2014), brazilian public entity. The hydrogeological information was obtained from the IMASUL database, the ambiental estate entity. As final results, is presented the feasibility of using GPR in the subsurface identification of lateritic cangas, in addition to the thickness definition of detritus-lateritic coverage, with definition of its contact with the other underlying formations; definition of the distribution and thickness of basalts the Serra Geral formation in the area and the definition of the potentiometric map of the aquifer represented by the TQdl coverage. The NNW-SSE geological profile was generated, seeking a better understanding of the geological-structural framework of the study area, where the TQdl coverage rests on the Bauru Group, about Serra Geral formation, on Botucatu formation, about Estrada Nova formations and over Aquidauana formation.